2018
DOI: 10.1111/jfb.13729
|View full text |Cite
|
Sign up to set email alerts
|

Parasite communities of the white seabream Diplodus sargus sargus in the marine protected area of Medes Islands, north‐west Mediterranean Sea

Abstract: Marine protected areas are considered a useful tool to preserve and recover the biodiversity of ecosystems. It is suggested that fisheries not only affect populations of target and bycatch species but also their parasite communities. Parasites can indicate fishery effects on host species and also on the whole local community, but the effects of fisheries and protection measures on parasite communities are relatively unknown. This study analyses parasite communities of the white seabream Diplodus sargus sargus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
(123 reference statements)
0
9
0
Order By: Relevance
“…Sparids have already collected this species by Hermida et al (2012) in the North Atlantic. Scolex pleuronectis larvae were identified with a prevalence of 23.07% and reported in Sparidae fish by several authors (Anato et al, 1991;Akmirza, 1998Akmirza, , 2000Akmirza, , 2002Paraguassù et al, 2002;Luque and Poulin, 2004;Perez-Del-Olmo et al, 2007, 2008Ternengo et al, 2009;Marzoug et al, 2012;Radujkovic et al, 2014, Benhamou et al, 2017and Isbert et al, 2018Hadjou, 2019).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Sparids have already collected this species by Hermida et al (2012) in the North Atlantic. Scolex pleuronectis larvae were identified with a prevalence of 23.07% and reported in Sparidae fish by several authors (Anato et al, 1991;Akmirza, 1998Akmirza, , 2000Akmirza, , 2002Paraguassù et al, 2002;Luque and Poulin, 2004;Perez-Del-Olmo et al, 2007, 2008Ternengo et al, 2009;Marzoug et al, 2012;Radujkovic et al, 2014, Benhamou et al, 2017and Isbert et al, 2018Hadjou, 2019).…”
Section: Resultsmentioning
confidence: 92%
“…Prevalence (P), abundance (Ab), and mean intensity (MI) of Nematoda in sparid fishes from the western Mediterranean coast of Algeria for the stomach (A), caecum (B), intestine(C), gonads (D), rectum(E), liver (F), general cavity(G), esophagus(H), digestive tract (I) sites. -Renaud & al., 1980-Cook & al., 1981-Petter & al., 1984-Petter et Maillard, 1988a, 1988b-Pérez -del -olmo et al, -Merzoug & al., 2012-Ichalal et al, 2015-Benhamou & al., 2017-Keser & al., 2007 Hadjou & al., 2017-Ternengo & al., 2009-Saadi & al., 2019-Ternengo & al., 2009-Isbert & al., 2018-Petter & al.,1984-Petter & Radujkovic, 1989-Radujkovic et Raibaut, 1989-Akmirza, 1998-Merzoug & al., 2012-Benhamou & al., 2017-Lablack, 2014-Lablack, 2014 [ Hadjou & al., 2017-Azbaid & al., 2016-Gasmi & al., -Saadi & al., 2019-Costa & al., 2004-Hermida & al., 2012-Lablack, 2014-Eiras & Rego, 1987-Vicente & al.,1985,1999-Paraguassù & al., 2000-Luque & Poulin, 2004-Saad & Luque, 2009-Lablack, 2014-Huang, 1988 [ Radujkovic & al., 2014-Pérez -del -olmo & al., 2007-Marzoug & al., 2012…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, most previous research has recorded higher parasite species richness, diversity and abundance in protected areas (Bartoli, Gibson, & Bray, 2005; Lafferty, Shaw, & Kuris, 2008; Loot, Aldana, & Navarrete, 2005; Sasal, Desdevises, Durieux, Lenfant, & Romans, 2004; Sasal, Faliex, & Morand, 1996; Wood et al, 2013), although other studies found no clearcut differences in assemblage structure (Ternengo, Levron, Mouillot, & Marchand, 2009) or opposite trends of abundance across parasite species (Isbert et al, 2018; Marzoug, Boutiba, Kostadinova, & Perez‐del‐Olmo, 2012). These effects on parasite communities have been used as indirect evidence on how fisheries can affect parasites (Wood & Lafferty, 2015) in a small number of studies (Isbert et al, 2018). However, probably because all these studies were carried out by comparison between fished and protected areas, little mention has been made of the potential of parasites as indicators of the success of protected areas in recovering ecosystems (but see Isbert et al, 2018), which should include data from before and after protection measures.…”
Section: Discussionmentioning
confidence: 98%
“…This includes fish parasites, which are impacted by reduced host abundance and food web complexity, which affect their transmission efficiency, population density and assemblage species richness (Wood & Lafferty, 2015). Understanding how parasite assemblages respond to protection measures may therefore help to evaluate the degree of effectiveness of fisheries management measures (Isbert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%